2020
DOI: 10.1039/c9ra10371f
|View full text |Cite
|
Sign up to set email alerts
|

Efficient biodegradation of petroleum n-alkanes and polycyclic aromatic hydrocarbons by polyextremophilic Pseudomonas aeruginosa san ai with multidegradative capacity

Abstract: Pseudomonas aeruginosa san ai degraded individual selected petroleum compounds: n-hexadecane, n-nonadecane, fluorene, phenanthrene, and pyrene with high efficiency, at initial concentrations of 20 mg L−1 and in seven days.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(51 citation statements)
references
References 59 publications
0
39
1
2
Order By: Relevance
“…Some comparable data, such as morphology, phenotype, and characterization of bacteria should be considered in the search for possible bacteria in PAHs biodegradation (Lloyd et al 2010;Marzuki et al 2016). Several factors explain the difference in the biodegradation activity of bacteria to PAHs, including 1) the properties of PAHs with a higher toxicity level of pyrene than naphthalene have an effect on the biodegradability of bacteria; 2) the characteristics and adaptability of bacteria to predators are different; and 3) the number of bacterial cells, the supply of nutrients and oxygen have contributed to the growth, development activity, and strength of the cells (Medić et al 2020). The amount of bacterial biodegradation activity against PAHs is determined on the basis of the biodegradation parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Some comparable data, such as morphology, phenotype, and characterization of bacteria should be considered in the search for possible bacteria in PAHs biodegradation (Lloyd et al 2010;Marzuki et al 2016). Several factors explain the difference in the biodegradation activity of bacteria to PAHs, including 1) the properties of PAHs with a higher toxicity level of pyrene than naphthalene have an effect on the biodegradability of bacteria; 2) the characteristics and adaptability of bacteria to predators are different; and 3) the number of bacterial cells, the supply of nutrients and oxygen have contributed to the growth, development activity, and strength of the cells (Medić et al 2020). The amount of bacterial biodegradation activity against PAHs is determined on the basis of the biodegradation parameters.…”
Section: Discussionmentioning
confidence: 99%
“…For n-alkanes (C 8 -C 40 ), the aerobic degradation is divided into three oxidation modes [124]. These modes are known as terminal oxidation [125], subterminal oxidation [126], and biterminal oxidation [127]. The oxidation modes take place at different carbon positions and form various end products.…”
Section: Mechanisms Involved In Diesel Bioremediation By Bacteriamentioning
confidence: 99%
“…The success of bioremediation is largely governed by the survival, adaptability and catabolic activities of the introduced microorganisms. Some of the bacterial strains successfully used for this purpose include Pseudomonas aeruginosa (san ai) (Medic et al 2020), Comamonas testosteroni BR60 (Gentry et al 2001), Pseudomonas putida ZWL73 (Niu et al 2009), Bacillus sp. (Kiamarsi et al 2018) etc.…”
Section: Introductionmentioning
confidence: 99%
“…The contaminated sites selectively promote growth of hydrocarbon degrading bacterial populations. Two bacterial genera namely Pseudomonas and Bacillus have been extensively reported from hydrocarbon contaminated sites (Das and Mukherjee 2007;Kiamarsi et al 2018;Medic et al 2020). Several studies have demonstrated active involvement of Pseudomonas (Bhattacharya et al 2003;Mulet et al 2011) as the most prominent hydrocarbon degrading bacterial genera.…”
Section: Introductionmentioning
confidence: 99%